Democracia participativa e a efetividade do controle social da Administração Pública no estado democrático de direito - Signorelli, Filipe Venturini (2023)
The general objective of this study is to analyze participatory democracy and the effectiveness of social control of Public Administration in the Democratic State of Law. We opted for a qualitative exploratory legal bibliographical research, carried out from research on legislation and applied doctrine. As purposes of bibliographical and documentary research, expansion of knowledge in a given area and the mastery of this science as an auxiliary instrument for the construction and foundation of the subject addressed in this work can be mentioned. At the end of the study, it is concluded that the direct participation of the individual citizen and the organized civil society in the Public Administration is the most concise way to guarantee that the construction of the Democratic State of Law will seek fairness in its evolutionary process, in particular, in the feeling of each individual, this form of control as a configuration of the democratic system can be seen as stabilizing the expected legal security, in which, State and society are intertwined through actions that can define the position of each one in the historical moment experienced